Identification and persistence of Pinus pollen DNA on cotton fabrics: A forensic application. Issue 1 (January 2016) - Schield, Cassandra; Campelli, Cassandra; Sycalik, Jennifer; Randle, Christopher; Hughes-Stamm, Sheree; Gangitano, David
Abstract: Advances in plant genomics have had an impact on the field of forensic botany. However, the use of pollen DNA profiling in forensic investigations has yet to be applied. Five volunteers wore a jacket with Pinus echinata pollen-containing cotton swatches for a 14-day period. Pollen decay was evaluated at days 0, 3, 6, 9 and 14 by microscopy. Pollen grains were then transferred to slides using a portable forensic vacuum handle. Ten single grains per swatch were isolated for DNA analysis. DNA was extracted using a high throughput extraction method. A nine-locus short tandem repeat (STR) multiplex system, including previously published primers from Pinus taeda, was developed. DNA was amplified by PCR using fluorescent dyes and analyzed by capillary electrophoresis. Pollen counts from cotton swatches in a 14-day period exhibited an exponential decay from 100% to 17%. The success rate of PCR amplification was 81.2%. Complete and partial STR profiles were generated from 250 pollen grains analyzed (44% and 37%, respectively). Due to the limited amount of DNA, drop-in events were observed (1.87%). However, the rate of contamination with pollen from other pine individuals originating from environmental sources was 4.4%. In conclusion, this study has shown that pollen can be a stable source of forensic DNA evidence, as a proof-of-principle, and that may persist on cotton clothing for at least 14 days of wear. This method can be applied in forensic cases where pollen grains larger than 10 μm (e.g., from herbs or trees) may be transferred to clothing (worn by suspect or victim) by primary contact. Highlights: Stability of pine pollen DNA on cotton fabrics over a 14-day period was studied. Pollen was collected and transferred to slides with a portable vacuum handle. DNA was extracted using a high throughput extraction method. Single grains (N = 250) were genotyped with a nine-locus STR multiplex system. Complete (44%) and partial (37%) STR profiles were generated.